Life as a breastfeeding-working-mother : understanding challenges and support systems that contribute to the success of breastfeeding among working-mothers in Indonesia : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Palmerston North, New Zealand - Swastiningsih, Nurfitria (Massey University, 2024)
Breastfeeding plays a crucial role in infants and children’s health and development. The success of breastfeeding in Indonesia is still below the expectancy rate set by Government Policy. Maternal employment is one of the reasons for breastfeeding discontinuation with mothers facing lack of support from the workplace. Despite the difficulties, there are mothers who successfully find balance while breastfeeding and working but research undertaken in this area is limited. This study aimed to analyse and better understand the lived experience of breastfeeding-working-mothers who successfully maintain long-term breastfeeding. Since mothers’ lives cannot be separated from their social context, a community psychology approach and ecological model is used to understand mothers’ experiences. Interpretative Phenomenological Analysis is employed as a methodological and analytic approach to interpret lived experience from an emic perspective. Data was collected using the semi-structured interviewed which conducted online during the Covid-19 pandemic. Twenty-four interviews were conducted across three participant groups including nine mothers who met the criteria as active breastfeeding-working-mothers having breastfed their babies for a minimum of eighteen months or having experience as breastfeeding-working-mothers for at least two years; seven husbands whose wives met the criteria of the breastfeeding-working-mothers group; and eight co-workers/supervisors of the breastfeeding-working-mothers. Including husbands and co-workers/supervisors was crucial to understand their perspectives and experiences, providing insights into the daily dynamics between mothers and their microsystems. Using the strength-based approach, I focused on understanding mothers’ successful experience to enable and promote more positive and sustaining experiences for other mothers and their community in the future. From the research analysis, multi-layered systems from micro to macrosystems present both supports and challenges for the breastfeeding-working-mothers. Microsystem support was most important to successful breastfeeding journeys as the closest relationships provided a safe space and the sense of security that strengthen mothers against the multi layered challenges in breastfeeding. Findings from this study suggests the importance of enhancing systemic support from micro to macrosystem. Breastfeeding education should involve the husbands and the family members who closely connected with the mothers to enhance the family support. Moreover, improving the healthcare and workplace support is necessary as well as enhancing the provisions of the government policy to create environments enabling working mothers to sustain breastfeeding.
Keywords: Breastfeeding-working-mother, interpretative phenomenological analysis, Indonesia, ecological model; 520304 Health psychology; 520501 Community psychology